The relationship between rapid naming and word spelling in English. (20th May 2013) - Stainthorp, Rhona; Powell, Daisy; Stuart, Morag
<x xml:space="preserve">Abstract</x> A study of the concurrent relationships between naming speed, phonological awareness and spelling ability in 146 children in Years 3 and 4 of state‐funded schools in South‐East England (equivalent to US Grades 2 and 3) is reported. Seventy‐two children identified as having normal phonological awareness but reduced rapid automatised naming (RAN) performance (1 standard deviation below the mean) participated in the study. A group of 74 children was further identified. These children were matched on phonological awareness, verbal and nonverbal IQ and visual acuity, but all members of this group showed normal RAN performance. RAN made a significant unique contribution to spelling performance. Further analyses showed that participants with low naming performance were significantly poorer spellers overall and had a specific difficulty in spelling irregular words. The findings support the view that RAN may be indexing processes that are implicated in the establishment of fully specified orthographic representations.